Nursing care in the rooming-in: the nurse’s view - Sampaio, Francisca Leonilda; Silveira, Isolda Pereira da (Rev Rene, 2005)
The study aimed at analyzing the nurse’s participation in the nursing care provided in the rooming-in and describing how the nurse perceives the nursing care to the puerperal woman and to the newborn. The study has been accomplished in the rooming-in at a public hospital in Fortaleza, CE. The participants were seven nurses that were assigned to this unit. The method for data collection was a semi-structured interview. It was carried out from December 2003 to February 2004. The results made possible the identification of the following categories: Concern with the puerperal woman’s acclimatization and well-being in the rooming-in; Absence of technical resources to complement the nursing care and the good course of the unit; Revealing affectivity in taking care; Promoting health education. It has been concluded that change on the part of the administrators, including the nursing ones, is possible, in order to provide the clientele with a more humane and quality stay.